The Importance of Being Political: Emergence of a Multi-stakeholder Forum at the Lake Malili Complex, South Sulawesi - Nurhady Sirimorok; Eko Rusdianto (Forest and Society, 2020)
Multi-stakeholder forums are considered an essential element of landscape approaches for sustainable development and integrated ecosystem management. Such forums are widely adopted in environmental management policies and introduced as precursors for novel institutional arrangements for collective action in complex landscapes. However, while they are often held up as a mechanism for greater inclusion and representation, they can also further marginalize less powerful stakeholders. In this respect, the importance of politics in shaping the success of a multi-stakeholder forum is often overlooked. This article examines different multi-stakeholder mechanisms for governing the Lake Malili Complex in Sulawesi, Indonesia —a landscape characterized by competing land use interests and the presence of threatened endemic species.  The case highlights a successful bottom-up multi-stakeholder approach that became a model for collaboration, and which was subsequently scaled up to cover the broader Lake Malili Complex area.. The research is based on longstanding participation in the politics of decision-making processes at the Lake Malili Complex, complemented by in-depth examination of the establishment of the multi-stakeholder forum. The findings show that strong, locally-based initiatives provide an avenue for generating greater participation in achieving mutual goals for conserving the Lake Malili Complex. However, participation in the multi-stakeholder platform is not enough to push for decision making at the district level, where more powerful management decisions take place. We therefore note that outcomes of community-based resource management are limited when they are not backed by more political approaches to influence decision making